Studies on the growth kinetics of lactic acid bacteria under controlled pH cultivation environmental using alginate capsules - Nur Shahira Mohd Nasir (School of Bioprocess Engineering, University Malaysia Perlis, 2013)
End-product inhibition in LAB fermentation has initiates the development of various approaches to minimize the inhibition effect on LAB growth. The inhibition effect can be minimized by controlling the pH in LAB fermentation. In this study, a novel method has been developed by encapsulating calcium carbonate (CaCO3) into alginate capsules. The capsules were produced by a simple dripping technique which is known as extrusion to control the pH during LAB fermentation. Capsules were formed by extruding the mixture of CaCO3, calcium chloride (CaCl2) and carboxylmethyl cellulose (CMC) through a needle into alginate solution containing sodium alginate and Tween 80. The diameter and membrane thickness of the capsules were varied to study their effects on growth kinetics of LAB.